Burkitt's Lymphoma in a 5 year old Bengali Girl: A Case Report - Chatterjee, I; Roy, A (Journal of Nepal Paediatric Society, 2011)
Burkitt's lymphoma (BL) is a rare monoclonal proliferation of B-lymphocytes and is classified as a poorly differentiated lymphocytic lymphoma. This tumor was first noted in Africans. The cause of this tumor is debatable, but strong evidence implicates Epstein-Barr virus in its development. This tumor predominantly affects children and is probably the fastest growing tumor in humans, with exuberant proliferation. It is a very rare malignancy accounting for only 0.76% of solid malignant tumors among Indian children. A case of BL of the right hemimandible in a 5-year-old Bengali girl is reported. Key words: Burkitt's lymphoma; Immunohistochemistry; Chemotherapy. DOI: 10.3126/jnps.v31i1.3903 J Nep Paedtr Soc 2010;31(1):61-63